Reproductive parameters of Chalcorana labialis (Anura: Ranidae) from Peninsular Malaysia - S. Shahriza,; J. Ibrahim,; M.S. Shahrul Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Egg clutches of Chalcorana labialis were collected from their natural habitat at Sungai Junjong, Kedah, between March 1998 and February 1999. Egg clutches were typically encountered in temporary pools, rock pools and isolated pools at the edge of the river. In the laboratory several reproductive parameters including clutch size, egg diameter, hatching and metamorphosis rates were measured. The mean ± SD (range, N) of clutch size, egg diameter, hatching and metamorphosis rates of C. labialis were 1365.4 ± 421.1 (787-2100, 10) eggs, 1.36 ± 0.15 (1.12-1.68, 20) mm, 97.30 ± 0.99% (95.87-98.86, 10) and 4.15 ± 0.74% (3.1-5.8, 10), respectively. These results indicated that the successfully rate of larvae to become froglets is relatively low, although it was reared in the laboratory. To keep survived, almost all species of frogs produced eggs in a large quantity.